A=(25³)^9:(4²+3²)^26-(2017^0+0^2017+1^2017)⁴=
Autor e urgent ofer 54 puncte ajutatima
Răspunsuri la întrebare
Răspuns de
14
A = (25^3)^9 : (4^2+3^2)-(2017^0+0^2017+1^2017)^4
A = 25^27 : (16+9)^26 - (1 + 0 + 1)^4
A = 25^27 : 25^26 - 2^4
A = 25^(27-26) - 16
A = 25 - 16
A = 9
A = 25^27 : (16+9)^26 - (1 + 0 + 1)^4
A = 25^27 : 25^26 - 2^4
A = 25^(27-26) - 16
A = 25 - 16
A = 9
Răspuns de
4
A=(25³)^9:(4²+3²)^26-(2017^0+0^2017+1^2017)⁴=
↓ ↓ ↓ ↓ ↓
= 25²⁷ : 25²⁶ - ( 1 + 0 + 1 )⁴ =
↓ ↓
= 25 - 16 =
↓
= 9
↓ ↓ ↓ ↓ ↓
= 25²⁷ : 25²⁶ - ( 1 + 0 + 1 )⁴ =
↓ ↓
= 25 - 16 =
↓
= 9
Alte întrebări interesante
Matematică,
8 ani în urmă
Matematică,
8 ani în urmă
Matematică,
8 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă